"Single‐cell multimodal chromatin profiles revealing epigenetic regulations of cells in hepatocellular carcinoma" - Vikas Kumar; Samuel Beck (Wiley, 2024)
Abstract Hepatocellular carcinoma (HCC), with its increasing prevalence globally, is emerging as a major health challenge. Hepatocellular carcinoma cells exhibit both significant homogeneity and heterogeneity, governed by complex epigenomic regulations. Recently, numerous single‐cell unimodal techniques have been used to study HCC at various levelswhich have already revealed a complex interplay at genomic, transcriptomic, spatial and epigenomic levels. However, the use of single‐cell multimodal techniques combining different unimodal layers in HCC remains quite limited, necessitating further studies focusing on these methods to uncover novel markers, and mechanisms at epigenetic levels. In this commentary, we highlight how integrating multimodal approaches with epigenetic modifications can provide new insights into HCC and foster future therapeutic advancements.